2022
DOI: 10.3390/diagnostics12092234
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Using Endobronchial-Ultrasound-Guided Transbronchial Needle Aspiration Image to Improve the Overall Diagnostic Yield of Sampling Mediastinal Lymphadenopathy

Abstract: Lung cancer is the biggest cause of cancer-related death worldwide. An accurate nodal staging is critical for the determination of treatment strategy for lung cancer patients. Endobronchial-ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has revolutionized the field of pulmonology and is considered to be extremely sensitive, specific, and secure for lung cancer staging through rapid on-site evaluation (ROSE), but manual visual inspection on the entire slide of EBUS smears is challenging, time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 56 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…To produce accurate and detailed segmentations, they defined a skip architecture that combines semantic information from a deep, coarse layer with appearance information from a shallow, fine layer. In recent years, researchers developed a modified FCN-32s approach and demonstrated that it is beneficial for tumor segmentation in the diagnosis of cervical cancer [ 7 ], thyroid cancer [ 6 ], breast cancer [ 8 ], ovarian cancer [ 10 , 11 ], and EBUS [ 9 ]. Shen et al [ 61 ] developed a modified mini-U-net to segment the touching cells accurately in FISH images and demonstrated that the performance is better than the original mini-U-net [ 62 ].…”
Section: Related Work In Soft Label Label Smoothing and Segmentation ...mentioning
confidence: 99%
See 4 more Smart Citations
“…To produce accurate and detailed segmentations, they defined a skip architecture that combines semantic information from a deep, coarse layer with appearance information from a shallow, fine layer. In recent years, researchers developed a modified FCN-32s approach and demonstrated that it is beneficial for tumor segmentation in the diagnosis of cervical cancer [ 7 ], thyroid cancer [ 6 ], breast cancer [ 8 ], ovarian cancer [ 10 , 11 ], and EBUS [ 9 ]. Shen et al [ 61 ] developed a modified mini-U-net to segment the touching cells accurately in FISH images and demonstrated that the performance is better than the original mini-U-net [ 62 ].…”
Section: Related Work In Soft Label Label Smoothing and Segmentation ...mentioning
confidence: 99%
“…Chen et al [ 40 ] proposed DeepLabv3+, a deep learning model with an encoder–decoder structure, and proved its efficacy on the Cityscapes dataset [ 65 ], which includes polygonal annotations of instance segmentation for vehicles and people. In our experiment, we compare the proposed method with the state-of-the-art deep learning models, including FCN [ 36 ], Modified FCN [ 6 , 7 , 8 , 9 , 10 , 11 ], U-Net [ 2 ] +InceptionV4 [ 32 ], Ensemble of U-Net with Inception-v4 [ 32 ], Inception-Resnet-v2 encoder [ 32 ], and ResNet-34 encoder [ 33 ], U-Net [ 2 ], SegNet [ 34 ], YOLOv5 [ 35 ], BCNet [ 39 ], CPN [ 37 ], SOLOv2 [ 38 ], and DeepLabv3+ [ 40 ] with three different backbones, including MobileNet [ 41 ], ResNet [ 33 ], and Xception [ 42 ].…”
Section: Related Work In Soft Label Label Smoothing and Segmentation ...mentioning
confidence: 99%
See 3 more Smart Citations